Interspecific Association Of Seagrass Enhalus Acoroides With Macrozoobenthos In Seagrass Meadow Ecosystems In The Eastern Part Of Pramuka Island - Angellica, Angellica; Septiya, Celsi Anggun; Klarisa, Fransiska Tika; Mulyaningsih, Linda; Reza, Mu'amar Huzaifi; Safinatunnaja, Nazhifa; Nuraulia, Renasya; Putri, Viranti Kartika; Agustina, Aprilia Dwi; Rasyid, Fadhli Muhammad; Razan, Haidar Fauzi; Kelana, Sania Anugrah (Jurnal Kelautan, 2024)
ABSTRACTThe seagrass community structure on Pramuka Island is declining due to human activities. The condition of the seagrass community structure can be seen from the stability of the ecosystem, where the diversity of macrozoobenthos in it can be one of the indicators that describe the condition of the seagrass. This study aimed to investigate the association between seagrasses and macrozoobenthos, as well as the distribution of macrozoobenthos in the eastern part of Pramuka Island. The quadrant transect method was used at three observation points with a 100 m transect and 1x1 m² plots at 10 m intervals. The physical and chemical parameters were measured at the start, middle, and end points of each transect using water and sediment samples. Enhalus acoroides dominated four seagrass species found in three transects. Plots near the shoreline and mangrove ecosystems harbored Macrozoobenthos due to sediment richness in the organic matter. The results showed that the correlation between Enhalus acoroides and the macrozoobenthos Holothuria atra had a perfect level of association. Enhalus acoroides plays an important role in providing habitat and food for macrozoobenthos on Pramuka Island. This symbiotic relationship maintains the balance of the seagrass ecosystem on Pramuka Island. The diversity of macrozoobenthos species found on Pramuka Island indicates that this ecosystem is relatively healthy and able to provide various resources for organisms residing in seagrass beds.Keywords: Association, macrozoobenthos, seagrass beds.